Do Mergers Among Multimarket Firms Create Value? - Sebastian Linde; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2016)
Merger value is frequently evaluated in single market contexts without considering possible gains stemming from firms' multimarket presence. This study concentrates on the question through which channels, and of which magnitude, mergers among multimarket firms create incremental value. We establish a simple theoretical model that determines merger value in a multimarket firm environment. The model enables us to derive merger values as being independent of post-merger market shares, but rather dependent on pre-merger market shares. We test our hypotheses using a comprehensive dataset that encompasses information on mergers and firm-level multimarket production and innovation within the semiconductor industry. Using the pairwise stable equilibrium concept, we estimate firms' structural value functions. Our results show that multimarket effects contribute, on average, 20% of the total merger value added. Moreover, we find that multimarket efficiency gains dominate multimarket power effects by contributing majority of the value added. We also find that our estimated merger values are well aligned with the merging firms' post-merger stock market performance.
Keywords: L10; L13; L20; 330; efficiency gains; market power; matching; merger formation; merger value; multimarket competition